Asset Management Information Systemin Private Islamic College Environment - Munifah; Aprilia, Try Heni; Hamida, Ulfi Dina (LETIGES, 2025)
Asset management requires a special method for its implementation so that the management information system can run optimally. The goal is for the system to be developed in the form of web-based software in an effort to optimize asset tracking at private Islamic religious colleges. The Analytical Hierarchy Process offers an alternative priority scale that will facilitate the decision-making process. This study will use a qualitative approach with the Research and Development method as a strategic step. The research object was conducted in two places, namely Hasyim Asy'ari University and the Bani Fattah Islamic Institute, Jombang. The results of the study show that both universities currently still rely on a manual system using Excel which is inadequate in terms of classification and automation. Hasyim Asy'ari University has a more structured approach to asset classification, while the Bani Fattah Islamic Institute, Jombang has not implemented systematic asset categorization. The four main stages in asset management are planning, organizing, implementing, and evaluating. Both universities face challenges in organizing and implementing asset management because there is no special information system. In addition, the evaluation process is carried out manually through periodic inventory checks, thus limiting efficiency in decision-making. This study proposes the development of a structured web-based asset management system with a clear framework for system design, implementation, and testing. The integration of Waterfall and AHP methodologies is expected to improve efficiency, data organization, and decision-making in asset management. This study contributes to this field by offering a strategic approach to move from a manual asset management system to an automated asset management system, which ensures better resource utilization and administrative efficiency.